Calligraphy and Its Role in Arabic Language Education - Mukarom, Arik Maghfirotul; Afriansyah, Dibi; Bakheet, Bakri Mohammad; Wargadinata, Wildana (MAN Insan Cendekia Siak, 2025)
This research aims to understand the science of calligraphy and its role in the process of Arabic language teaching. As is known, the science of calligraphy is the art of writing Arabic letters in a beautiful and artistic manner. This can make text more engaging and aesthetic, which in turn can motivate students to deepen their understanding of the Arabic language. The methodology employed in this research is library research. The findings of this study indicate that teaching Arabic calligraphy art requires instructional steps, namely: determining learning objectives, designing learning activities, and evaluating learning outcomes. This research also reveals that Arabic calligraphy art plays an important role in Arabic language teaching through enhancing students’ writing abilities, enriching students’ Arabic vocabulary, increasing their knowledge of Arabic language structure, and strengthening students’ interest and motivation.